Humanisation of Spiritual Education in Fostering Marginalized Communities at Majelis Ta'lim Sabilu Taubah - Wibowo, Arif (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Amar ma'ruf nahi munkar is Allah's command to all of us Muslims. As whatever we are wherever we are in whatever position we are. We can fulfil amar ma'ruf nahi munkar according to our abilities, for those who have power through their power, for those who are able to with their mouths then with their tongues, even for those who are unable to do even the smallest amount are still exposed to khat to fulfil with their hearts. Through this research, the author aims to find out how the effectiveness of da'wah that sees from the side of the need and the need for a touch of qolbu through spiritual education as a solution to build basic human awareness (fitroh) individually and socially, which is packaged in accordance with the development of modern times today, which is carried out at Majelis Taklim Sabilu Taubah to marginalised communities. In discussing this research, the author uses a qualitative approach with descriptive characteristics. The da'wah activities at the Sabilu Taubah Ta'lim were founded by Kyai Agus Muhammad Iqdam Kholid or commonly called Gus Iqdam. In this ta'lim assembly, it is very unique unlike other Ta'lim assemblies because the congregation of this ta'lim assembly is mostly from marginalised communities. From this research it can be concluded that the da'wah activities carried out at Majelis Taklim Sabilu Taubah are very effective and appropriate in this modern era by looking at (1) the enthusiasm of the audience following the da'wah study is getting higher and higher (increasing), (2) the dialogical approach taken makes the audience very interested, because there are elements of problem solving and rewards for economic em powerment, (3) the contextuality of the media according to the times so that it makes the audience interested not boring, and (4. the method of delivering spirituality planting material that is relaxed so that it can reach the audience.